Analisis Penerapan Costing Volume Profit (CVP) Pada Kinerja Keuangan Tuwa Kawa Coffee & Eatry - Maharani Rahayu, Nabila; Astuti, Widia (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Tuwa Kawa Coffee & Eatry as a business actor in the culinary sector needs to ensure profit stability amid fluctuations in operational costs and uncertain sales volumes. In practice, the company has not used the right financial analysis tools to help with profit planning in a systematic and measurable manner. This study aims to analyze Costing Volume Profit (CVP) for profit planning at Tuwa Kawa Coffee & Eatry. CVP analysis serves to identify the relationship between costs, sales volume and profit so that it can provide an overview of changes in one of the components that will affect the company's profit. The research method applied is a case study with a qualitative descriptive approach. The data analyzed was obtained from the financial statements of Tuwa Kawa Coffee & Eatry's profit and loss. The results of the study revealed that CVP analysis can provide significant benefits for management in estimating profits to be achieved, determining realistic sales targets and designing more efficient cost control strategies. In addition, CVP also assists management in evaluating the sensitivity of profits to changes in costs and selling prices so that business decisions can be made on a more accurate basis of analysis. Thus, the implementation of Costing Volume Profit (CVP) at Tuwa Kawa Coffee & Eatry is expected to be an important basis in financial planning and strategies to increase the company's profitability in the future.